Regional disparities of full pentavalent vaccine uptake and the determinants in Ethiopia: Mapping and spatial analysis using the EDHS data. - Getasew Mulat Bantie; Melaku Tadege; Teshager Zerihun Nigussie; Ashenafi Abate Woya; Abay Kassa Tekile; Amare Alemu Melese; Simeneh Ayalew; Belay Bezabih Beyene; Gizachew Yismaw Wubetu (PLoS ONE)
Background The full pentavalent (DPT-HepB-Hib) vaccination is the main strategy to prevent five communicable diseases in early childhood, especially in countries with huge communicable disease burdens like Ethiopia. Exploring spatial distributions and determinants of full pentavalent vaccination status in minor ecological areas in Ethiopia is crucial for creating targeted immunization campaigns and monitoring the advancement of accomplishing sustainable development goals. This study aimed to investigate the spatial disparities and determinants of full pentavalent vaccination among 12-23-month-old children in Ethiopia. Method The data on pentavalent vaccine uptake was found in the Ethiopian Health and Demographic Survey (EDHS, 2019). A two-stage cluster sampling method was applied to collect the EDHS data. The enumeration area was the primary sample unit while the household served as the secondary sampling unit. The geographical variations of full pentavalent vaccine uptake were explored using Quantum Geographic Information System (QGIS) software. The significant predictors of full pentavalent vaccination were identified using a simple logistic regression model through R version 4.1 software. Result The national full pentavalent vaccine uptake was 59.2%. The spatial distribution of full pentavalent vaccine uptake was not uniform in Ethiopia. Spatial cluster analysis revealed that most of low coverage regions for full pentavalent vaccine uptake were Afar, Somali, and Harari. The regions with the highest and lowest rates of vaccine uptake were Tigray and Harari region, respectively. Maternal age of 35-49 years (AOR = 3.42; 95% CI: 1.99, 5.87), and 25-34 years (AOR = 1.55; 95% CI: 1.17, 2.19), primary education attended (AOR = 1.51; 95%CI: 1.07, 2.11), richness wealth index (AOR = 1.96; 95% CI: 1.40, 2.75), birth order of 1-3 (AOR = 1.88; 95% CI: 1.19, 2.96), and delivery in the health facility (AOR = 3.41: 95% CI: 2.52, 4.61) were the determinants of full pentavalent vaccine uptake in Ethiopia. Conclusion Ethiopia's full pentavalent vaccine uptake was far lower than the global target. Older maternal age, maternal education, wealth index, birth order, and giving birth in a health facility were the determinants of full pentavalent vaccine uptake. Special attention should be given to Afar, Somali, and Harari regions, to strengthen the vaccine uptake. Moreover, improved socioeconomic status and getting maternal health services during delivery are necessary to enhance vaccine uptake.